Scientific and Technological Development in the Soviet Union (1917-1991): A Synopsis - Díaz Bolaños, Ronald Eduardo (2018)
Throughout its existence, the Union of Soviet Socialist Republics (USSR) experienced a series of political, economic and social transformations that converted the former Tsarist Russian Empire of agricultural economic base, into a superpower characterized by its progressive industrial development. In this process, which ranged from the triumph of the Russian Revolution (1917) to the dissolution of the Soviet Union (1991), scientific and technological development was fundamental due to the support that the Soviet State provided to science and technology in the construction of a socialist economic model, a process that experienced its contradictions under Stalinism and that received a significant stimulus with the development of the arms race and space exploration during the Cold War. The changes experienced by the Soviet Union in the 1980s were also reflected in its techno-scientific development.